2015
DOI: 10.1097/coc.0b013e3182940ff9
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Chemoradiation-related Lymphopenia and Clinical Outcomes in Patients With Locally Advanced Pancreatic Adenocarcinoma

Abstract: Objectives Lymphopenia is a common consequence of chemoradiation therapy yet is seldom addressed clinically. This study was conducted to determine if patients with locally advanced pancreatic cancer (LAPC) treated with definitive chemoradiation develop significant lymphopenia and if this affects clinical outcomes. Methods A retrospective analysis of patients with LAPC treated with chemoradiation at a single institution from 1997 to 2011 was performed. Total lymphocyte counts (TLCs) were recorded at baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(141 citation statements)
references
References 45 publications
10
129
2
Order By: Relevance
“…RIL is associated with treatment of many tumors (lung, colon, pancreas, breast, sarcomas, and glioblastoma) and associated with poor clinical outcomes (2,3,5,6). The biologic mechanisms leading to RIL are not clearly understood.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RIL is associated with treatment of many tumors (lung, colon, pancreas, breast, sarcomas, and glioblastoma) and associated with poor clinical outcomes (2,3,5,6). The biologic mechanisms leading to RIL are not clearly understood.…”
Section: Resultsmentioning
confidence: 99%
“…The biologic mechanisms leading to RIL are not clearly understood. T-cell renewal occurs approximately every 60 to 90 days (2,5). If the effect of radiation was only on circulating lymphocytes, and assuming that all circulating T cells were destroyed by irradiation, lymphopenia should not be observed for more than 90 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased conformity of proton therapy spares circulating lymphocytes through decreased radiation exposure and fractionation to major blood pools, such as the heart. Other research has shown that lymphopenia and post treatment circulating lymphocyte levels are independent predictors of survival (22,23). These collective findings suggest that proton therapy may improve outcomes through lymphocyte sparing.…”
Section: Editorialmentioning
confidence: 68%
“…The majority of patients who have pancreatic cancer in their initial evaluation have a combination of factors, such as advanced age, poor performance status, medical comorbidity or tumour-related conditions, such as anorexia; thus, they are poor candidates for aggressive therapy, such as CRT. It is important to perform a stratification of patients into treatment groups on the basis of prognostic factors (16,17).…”
Section: Discussionmentioning
confidence: 99%